Genome-Wide DNA Polymorphism Analysis and Molecular Marker Development for the Setaria italica Variety “SSR41” and Positional Cloning of the Setaria White Leaf Sheath Gene SiWLS1 - Zhang, Hui; Tang, Sha; Schnable, James C.; He, Qiang; Gao, Yuanzhu; Luo, Mingzhao; Jia, Guanqing; Feng, Baili; Zhi, Hui; Diao, Xianmin (Frontiers in Plant Science, 2021)
Genome-wide DNA polymorphism analysis and molecular marker development are important for forward genetics research and DNA marker-assisted breeding. As an ideal model system for Panicoideae grasses and an important minor crop in East Asia, foxtail millet (Setaria italica) has a high-quality reference genome as well as large mutant libraries based on the ‘Yugu1’ variety. However, there is still a lack of genetic and mutation mapping tools available for forward genetics research on S. italica. Here, we screened another S. italica genotype, ‘SRR41’, which is morphologically similar to, and readily cross-pollinates with, ‘Yugu1’. High-throughput resequencing of ‘SSR41’ identified 1,102,064 reliable single nucleotide polymorphisms (SNPs) and 196,782 insertions/deletions (InDels) between the two genotypes, indicating that these two genotypes have high genetic diversity. Of the 8,361 high-quality InDels longer than 20 bp that were developed as molecular markers, 180 were validated with 91.5% accuracy. We used ‘SSR41’ and these developed molecular markers to map the white leaf sheath gene SiWLS1. Further analyses showed that SiWLS1 encodes a chloroplast-localized protein that is involved in the regulation of chloroplast development in bundle sheath cells in the leaf sheath in S. italica, and is related to sensitivity to heavy metals. Our study provides the methodology and an important resource for forward genetics research on Setaria.